A hybrid algorithm for the load flow analysis of VSC-HVDC systems based on 1+2 order Newton-Raphson and simplified Newton - Wei, Yanfang; Li, Qiankun; Liu, Kang-Zhi; Wang, Peng; Zeng, Zhihui; Wang, Xiaowei (International journal of electrical power & energy systems, 2020)
•An efficient hybrid method is proposed for the load flow of VSC-HVDC.•The method is based on 1+2 Newton and simplified Newton methods.•A dimension reduction treatment for Jacobian matrix of VSC-HVDC is used.•Rule of thumb to select the iteration number of 1+2 Newton method is given.•Depth tests are carried out and the efficiency of the method is validated. With the rapid increase of multi-terminal and multi-infeed VSC-HVDC lines, the dimension and scale of AC/DC system equation and Jacobian matrix (JM) increase sharply, which makes the load flow (LF) analysis very complicated. In this paper, a new hybrid method is proposed to address this issue. This hybrid algorithm is composed of a 1+2 order Newton-Raphson (NR) method and a simplified Newton (SN) method. Specifically, the 1+2 order NR method is executed up to a preset number of iterations first, then the algorithm is switched to the SN until the system accuracy is met. A good compromise between the solution accuracy and computation burden can be achieved once a suitable iteration number is preset. To this end, a unified iterative form suitable for solving the LF of AC/DC systems with VSC-HVDC is derived in detail: a dimension reduction treatment is proposed to solve the problem of increasing dimension of JM; a rule of thumb is provided for the determination of the iteration number of 1+2 order NR. Then, the proposed hybrid method is validated on the modified IEEE-14, 30, 57 and 118 test systems. Comparisons and analyses are made for numerous scenarios, including the basic test of LF, different control modes and control objectives, influence of active and reactive powers on VSC parameters, algorithm performance under various initial states and heavy loading, etc. Compared with Newton and 1+2 order NR methods, the hybrid method shows a significantly shortened convergence time, 30% of 1+2 order NR and 47% of Newton on average.